1918 New Orleans Police Code at 114-16, image 112-14, Art. 15 (1918). - (:unkn) unknown (General Publisher, 1918)
Ship captains are obliged, within 24 hours of their arrival at port, to deposit gunpowder they may have on board in the powder magazine on the right bank of the river. Also prohibited citizens from storing more than one hundred pounds of gunpowder at any time.
--
Keywords: GUN POWDER TRANSPORTATION